STOMATOLOGICAL STATUS, CLINICAL DESCRIPTION OF ACUTE FESTERING SUBMANDIBULAR LYMPHADENITIS OF CHILDREN AND IMMUNOHISTOCHEMICAL CHANGES IN STRUCTURE OF GINGIVAL MARGIN - Lobach, Yu.B. (World of Medicine and Biology, 2013)
This article presents the data regarding the representation of clones of immunocompetent cells in the mucosa of the gingival margin of the mandible in acute purulent submandibular lymphadenitis in 36 children within the age range of 7 – 12 years. It is determined that intensity level of changes of immunohistochemical architectonics directly depends on the type of probable etiological factor that contributing to abscess formation in the lymph node, especially when it comes to its odontogenic origin.